Giant cell tumor stromal cells: osteoblast lineage-derived cells secrete IL-6 and IL-10 for M2 macrophages polarization - Yang, Kuan; Bao, Lihui; He, Xiaoning; Zhao, Wanmin; Fei, Dongdong; Li, Bei; Xue, Yang; Dong, Zhiwei (PeerJ, 2020)
Background The giant cell tumor (GCT) is a benign tumor which consists of three types cells: mononuclear histiocytic cells (MNHCs), multinuclear giant cells (MNGCs), and GCT stromal cells (GCTSCs). Numerous studies claim that GCTSCs have mesenchymal stem cells (MSCs) characters and play an important role in osteoclastogenesis; however, there are no research studies concerning macrophage polarization among GCT, which can be regarded as an ingredient for tumor aggression. Method We tested the effect of GCTSCs from three GCT samples which were collected from patients on proliferation, apoptosis and polarization of macrophage. Result In this article, we verified that GCTSCs expressed MSCs markers and had higher proliferation and relative lower differentiation abilities compared with BMMSCs. What’s more, we found a higher proportion of M2 macrophages among neoplasm. Co-culturing GCTSCs with macrophages resulted in prominent macrophage M2 polarization and increased the release of IL-6 (Interleukin-6) and IL-10 (Interleukin-10)from GCTSCs. In conclusion, GCTSCs, as originating from MSCs, can secret IL-6 and IL-10, which may play a significant role in macrophage M2 polarization.
Keywords: Giant cell tumor stromal cells; Macrophages; Polarization; Interleukin-6; Interleukin-10